Distraction Osteogenesis for Micrognathia in Cipto Mangunkusumo Hospital : A Case Series - Boaz, Grace; Kreshanti, Prasetyanugraheni; Handayani, Siti; Bangun, kristaninta (Jurnal Plastik Rekonstruksi, 2013)
Background: Micrognathia is usually associated with genetic syndromes, characterized by mandibular hypoplasia causing a receding chin. The overall incidence of micrognathia was 1 per 1600 births, makes it a rare case. Severe micrognathia can be a neonatal emergency due to airway obstruction by the tongue in the small oral cavity. One method for correcting micrognathia is distraction osteogenesis. Lack of experience due to rare incidence of case, expensive cost of distraction device and technical complexity of the operation can be obstacles to this management. Patient and Method: We report two cases of micrognathia corrected with distraction osteogenesis conducted in Cipto Mangunkusumo Hospital from 2011-2012. The method consists of implantation of bilateral distraction device to the inferior border of the mandibular body. The patients then followed postoperatively. Result: Mandibular lengthening by gradual distraction is a proper method for young patients with micrognathia. Despite our minimal experience and intricate kind of method, we are trying to improve our skill in the future. Summary: Distraction osteogenesis is one method for correcting congenital mandibular hypoplasia.